Web-based recruitment: effects of information, organizational brand, and attitudes toward a Web site on applicant attraction - Allen, David G; Mahto, Raj V; Otondo, Robert F (Journal of applied psychology, 2007)
Recruitment theory and research show that objective characteristics, subjective considerations, and critical contact send signals to prospective applicants about the organization and available opportunities. In the generating applicants phase of recruitment, critical contact may consist largely of interactions with recruitment sources (e.g., newspaper ads, job fairs, organization Web sites); however, research has yet to fully address how all 3 types of signaling mechanisms influence early job pursuit decisions in the context of organizational recruitment Web sites. Results based on data from 814 student participants searching actual organization Web sites support and extend signaling and brand equity theories by showing that job information (directly) and organization information (indirectly) are related to intentions to pursue employment when a priori perceptions of image are controlled. A priori organization image is related to pursuit intentions when subsequent information search is controlled, but organization familiarity is not, and attitudes about a recruitment source also influence attraction and partially mediate the effects of organization information. Theoretical and practical implications for recruitment are discussed.